Monetary policy in Switzerland: The performance during the seventies - Reinhard Fürstenberg (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1980)
This paper deals with some questions concerning monetary policy in Switzerland. Switzerland is an interesting case to study because the country is relatively small and correspondingly the total amount of Swiss franc holdings in the Swiss commercial banking System and in the Euromarkets is small in comparison to the same figures for some other currencies. The Swiss franc, however, appears to be subjected to remarkable changes in its appreciation by foreigners. Periods of strongly rising demand for the Swiss franc were followed by much more constricted views of the international community of wealth holders on the potential to gain from holding Swiss francs. Periods of sharp real appreciations were followed by intervals of time during which the Swiss franc depreciated even in nominal terms. Thus the central bank of Switzerland has to perform a rather difficult task because is faces obstacles which appear magnified when compared to other countries. This study sorts out the goals of Swiss monetary policy, and it also provides some normative Statements which will be put forward hesitatingly, and with due caution because the relevant monetary theory still is in a process of being created.
Keywords: 330